Policing and Sense of Place: ‘Shallow’ and ‘Deep’ Security in an English Town - Bradford, Ben (The British journal of criminology, 2024)
Much policy discourse concentrates on the contribution police make to keeping people safe. Often, this means minimizing fear of crime. Yet, more expansive accounts stress the extent to which deeper-rooted forms of security and belonging might also be important ‘outcomes’ of police activity. Using data collected from a survey of residents of a mid-sized English town, Macclesfield in Cheshire, we consider the extent to which evaluations of policing are associated with (1) a ‘shallow’ sense of security—roughly speaking, feeling safe—and (2) a ‘deeper’ sense of security—being comfortable in, and with, one’s environment. Focussing more accurately on the forms of safety and security police can hope to ‘produce’ opens up space for consideration of the ends they seek as well as the means they use.